Is Chronic Low Back Pain Associated with the Prevalence of Coronary Heart Disease when Genetic Susceptibility Is Considered? A Co-Twin Control Study of Spanish Twins. - Matt Fernandez; Juan R Ordoñana; Jan Hartvigsen; Manuela L Ferreira; Kathryn M Refshauge; Juan F Sánchez-Romera; Marina B Pinheiro; Stephen J Simpson; John L Hopper; Paulo H Ferreira (PLoS ONE, 2016)
OBJECTIVE:To investigate the chronic low back pain and coronary heart disease relationship, after adjusting for relevant confounders, including genetics. METHODS:In a cross-sectional design, 2148 twins were recruited from the Murcia Twin Registry, Spain. The exposure was chronic LBP and the outcomes were myocardial infarction and other coronary heart diseases-lifetime and in the last 2 years-based on standardized health-related questionnaires. First, logistic regression analysis investigated associations of the total sample followed by a matched co-twin control analyses, with all complete twin pairs discordant for chronic LBP utilised, separated for zygosity-dizygotic (DZ) and monozygotic (MZ) pairs, which adjusted for shared familial factors, including genetics. RESULTS:Chronic LBP pain is associated with lifetime myocardial infarction [odds ratio (OR) = 2.69, 95% confidence interval (CI) = 1.35-5.36], other coronary heart diseases over a lifetime (OR = 2.58, 95% CI: 1.69-3.93) and in the last two years (OR = 2.19, 95% CI: 1.33-3.60), while there was a borderline association with myocardial infarction in the last 2 years (OR = 2.64, 95% CI: 0.98-7.12). Although the magnitude of the association remained or increased in the co-twin control analyses, none reached statistical significance. CONCLUSION:Chronic LBP is associated with a higher prevalence of myocardial infarction and coronary heart disease. It is possible that this association remains even when controlling for genetics and early shared environment, although this should be investigated with larger samples of twins discordant for LBP.